Character Variable Model Determination of Regional Potential Decisions Using Driven Data - et al., Taufiq (International Journal of Advanced Science and Technology, 2019)
Regional potential is an ability that exists in an area that can be developed and is able to provide benefits to the people of the area which includes agriculture, plantation and fisheries. Regional potential is also a supporter of the national economy and optimal management planning is needed. The problem that arises in regional potential management planning is that the data to be processed is large-scale data and there is uncertainty. To overcome this problem, Data Driven is needed so that the Charakter Variable Model is Determined for Decision of Regional Potential Using Data Driven Case Study of Bireuen District, Aceh Province, July District. The desire to improve human decision making motivates the development of various modeling tools in economic disciplines, operations research, decision theory, decision analysis, and statistics. In each of these modeling tools, knowledge of a system is represented by algebraic, logical or statistical variables. Interactions between these variables are expressed by logical equations or rules, which may be enhanced by explicit representations of uncertainty, such as air, the state of natural potential.